Exploring the Evolution of Aspiration of Life in Scientific Literature: A Bibliometric Analysis (2015-2024) - Karki, Tej Bahadur; D’Mello, Laveena; Mahat, Dipak; Shrestha , Sajeeb (International Research Journal of MMC, 2024)
Objective: This bibliometric analysis explores the scholarly landscape of "Aspirations of Life" publications from 2015 to 2024, shedding light on trends, gaps, and key insights in this evolving field. The primary objective of this study is to identify the trajectory of research on aspirations, particularly focusing on the Nepalese context.Methodology: Utilizing bibliometric analysis, this study examined online scholarly articles published in Dimension.ai, employing statistical techniques to analyze publication trends, citations, and research patterns. This method provided a comprehensive overview of the research landscape by scrutinizing authors, keywords, citations, and publication years.Key Findings: The analysis revealed a significant increase in publications on "Aspirations of Life" over the past decade, peaking in 2023 with 532 publications. This surge underscores the growing scholarly interest in aspirations, with a notable rise in citations between 2020 and 2023, indicating increasing recognition and relevance in academic circles. However, a decline in the percentage of cited publications and fluctuating citation ratios suggest a need for more consistent impact and recognition of individual research contributions.Conclusion & Recommendation: The study highlights the escalating importance and relevance of research on "Aspirations of Life," emphasizing the need for enhanced impact and quality in scholarly articles. To bolster research influence, increasing the publication of high-quality articles in international peer-reviewed journals is crucial. Furthermore, addressing research gaps, such as longitudinal studies on aspiration changes over time and exploring cultural variations, can enrich our understanding and inform more effective interventions in this critical area of study.